Evaluasi Sistem Informasi Penjualan Kredit dan Piutang Dagang - Karmawan, I Gusti Made (Bina Nusantara University, 2011)
This study evaluates the implementation of management control and internal controls in application of sales systems information as a basis to support and produce accurate information in decision making. The methods used are bibliography study, interview, observation and questionnaire in the form of check lists. Following is an analysis conducted on the survey findings and the identification of strengths and weaknesses of internal control. Then audit is performed using Audit around the Computer method. From the evaluation results obtained the strengths and weaknesses of internal control. Weaknesses are found to be expressed in the form of problem findings, the potential risks and recommendations for corrective actions. This study succeeded in obtaining the evaluation results for boundary control, input, output, security and operational in the information system of credit sales and account receivables.